Alternative media and normative theory: A case study of Ferguson, Missouri - Poepsel, Mark Anthony; Painter, Chad (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2016)
This paper, based on in-depth interviews with journalists at alternative and advocacy papers in St. Louis as well as interviews with live streaming protestors, a new breed of citizen journalist, applies six characteristics commonly associated with the alternative press to coverage of the protests and police crackdown in Ferguson, Missouri between August 9, 2014 and March 2015. Journalists from the alternative newspaper in St. Louis focused on progressive or radical values less than the literature predicted. The African-American newspaper in St. Louis found itself influencing the national and global agenda regarding Ferguson and the ongoing oppression of blacks in the city and surrounding municipalities. Mobile media savvy protestors broadcast police actions from the front lines of dissent in nearly constant live streams day after day from August to November, altering the scope of counternarrative and providing distilled counter-propaganda. In this study, researchers provide a snapshot of the alternative/advocacy press as it rose to fill in gaps in coverage and to find untold stories in one of the most widely broadcast events of 2014.
Keywords: Ferguson; alternative news media; advocacy press; qualitative method; normative theory; live streaming